What are the factors that contribute to student engagement in synchronous and asynchronous online learning modalities? a qualitative descriptive study - Nava, Ina Katalina L. (Animo Repository, 2021)
The sudden shift to online modalities left students, so accustomed to face-to-face classes, wary and even fearful of remote learning. Teachers were similarly unprepared and struggled to find ways to maintain their students' motivation in virtual classrooms. With fully online education as the current reality in tertiary education in the Philippines, educators need to identify ways to increase learning by enhancing engagement. Through a qualitative descriptive study, the researchers explored how students’ engagement is affected by different factors related to online education. By conducting online interviews with 20 tertiary students - 10 male and 10 female, the researchers connected common themes and factors that students recognized as having effects on their engagement. Aside from allowing and encouraging all interviewees to share their opinions on online class, the researchers zeroed in on the participants' experience with the two most common online modalities - synchronous and asynchronous classes. The researchers found that there were common experiences, patterns, and preferences among participants. Commonalities among factors affecting engagement included difficulties adjusting, types of assignments given, preferences for certain styles of teaching, and prioritizing certain assignments over others. The researchers expect that this study will help the educational community find ways to foster engagement and thus improve learning outcomes when educating students online. Keywords: Engagement, Disengagement, Synchronous, Asynchronous, Experience